ENT300 Miracle Pet-Shop Sdn.Bhd / Mohd Hafizzi Majid... [et.al] - Majid, Mohd Hafizzi; Maurice Gurang, Kriztni Dami; Zulkarnain, Rafidah; Kassim, Nur Amni; Ahmad Fauzi, Muhammad Zhafri (2015)
To make it more seriously, we decided to make some innovation by decorating our own shop and special services for animal with a special price. Nowadays, the price of services is one of the important thing in any business attraction to people, We have done some research that Malaysia is one of developed country and many people in Malaysia love animal. Normally people who work during office hour and students have to go for school Monday until Friday. So, with our new innovation is that we create a special package services and promotion in selling the accessories of animal like food and others in Saturday. we are hoping and wishing to make MIRACLE PET SHOP SDN.BHD able to achieve outstanding demand from customer. Our business is expected to commence on 2015 and our vision is to make our company a well-known, established and satisfied by our customer in order to expand our pet shop to attract other pet shop company to deal with us with a better price. This will be realized by the full cooperation and efforts among the partners to promote company. Based on the objectives above, we are venturing into Pet business Industry. Animal companion has the potential of being a profitable business if it is done in modern way with large scale and systematically managed. We will expect that our business will become more developed in the near future because with the new innovation in our pet shop, the demand will Increase year by year. This will give more advantages for us to make our pet shop more profitable and stable in the long run.